Towards a Muslim Family Law Act? Debating Muslim women's rights and the codification of personal laws in India - Jones, J (Routledge, 2019)
Muslim personal laws in India have never been systematically codified, in marked contrast both to Hindu family laws in India and to Islamic family laws in much of the Muslim-majority world, both of which have been subject to a far greater degree of codification. This article examines the call being made by one prominent contemporary Muslim women's organisation, the Bharatiya Muslim Mahila Andolan (BMMA), for the wholesale codification of Muslim family laws in India as a pathway to protecting women's rights. Following a discussion of the wider context of India's uncodified Muslim personal law system, this paper offers a commentary on the BMMA's draft Family Law Act, first released in 2014. It demonstrates how this document synthesises discourses of women's rights drawn from a series of Qur’anic, constitutional and transnational reference points. By drawing from such diverse sources, and while legal codification in much of the Islamic world has instituted fundamentally patriarchal legal norms, the BMMA's proposed code articulates a distinctive, more gender-equal reading of Islamic family law.